Large tracheoesophageal granular cell tumor: An atypical case presentation, location, and management. (March 2022) - Diaz, Ashley; Yan, Kenneth; Cipriani, Nicole A.; Blair, Elizabeth A.
Abstract: Introduction: Granular cell tumors (GCT) are rare tumors that most frequently present in the oral cavity. While some present within the gastrointestinal tract, a GCT near the trachea is an extremely rare occurence. Presentation of case: A 42-year-old man presented to the Emergency Department after a motor vehicle accident. A computerized tomography (CT) scan revealed an incidental soft tissue 3.2 × 5.5 cm mass anterior to the esophagus and posterior to the trachea with no adjacent lymphadenopathy. The patient denied dyspnea, voice changes, or dysphagia. Due to its size and location, the patient underwent a transcervical excision of the retrotracheal tumor. Tumor cells were positive for CD68, CD163, S100, and SOX10, confirming a GCT. Conclusion: This is a distinctive presentation of a large (5 cm) GCT in the plane between the trachea and esophagus. GCTs are not often on the differential diagnosis of masses that present in this region. Highlights: Granular cell tumors (GCT) are rare tumors of the head and neck. A 42-year-old man presented to the Emergency Department after a motor vehicle accident with a 3.2 × 5.5 cm mass anterior to the esophagus and posterior to the tachea. The patient underwent a transcervical excision of the retrotracheal tumor, which was positive for CD68, CD163, S100, and SOX10, confirming a GCT. This is a distinctive presentation of a large (5.5cm) GCT in the plane between the trachea and esophagus that hasn't been shown in the literature